Alternative Strategy for Teaching and Learning during COVID-19 pandemic – A case study from Middle East College, OMAN - Najah Samiha; Rao Vikas; Al Qassabi Suad (SHS Web of Conferences, 2023)
Education witnessed great evolution thanks to Technological advances (Raja and Nagasubramani 2018). Although Online learning has many benefits such as flexibility and scalability, many higher education institutions do not opt to it since it was considered less effective than traditional classrooms. The outbreak of COVID19 pandemic and Social distancing measures taken in most countries in the world have revived the need for Online learning and greatly impacted the educational landscape. In this research, we target to study the effectiveness of online teaching through a case study from Middle East College during Spring 2020 semester. A layered approach has been adopted in the form of methodology which could be further elaborated and customized as per the nature and level of module. To this end, assessment of online teaching implementation from both teacher’s point of view and student’s perspective have been accomplished. Challenges will then be analyzed and recommendations in the future will be suggested.